PERAN BRAND IMAGE DALAM MEMEDIASI PENGARUH WOM TERHADAP SWITCHING INTENTION KE PRODUK SMARTPHONE MEREK SAMSUNG DI DENPASAR - Pelupessy, Selvina Juliana; Wardana, I Made; Suprapti, Ni Wayan Sri (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2017)
This study was conducted to determine the role of brand image in mediates the influence of WOM on switching intention to smartphones, the Samsung brand in Denpasar. The study population was people in Denpasar which do not have a smartphone Samsung brands. Respondents in this study were 120 people. The data analysis technique used is by using Structural Equation Modeling (SEM). The results showed that WOM positive and significant impact on the brand image, WOM positive and significant effect on the switching intention, brand image and significant positive effect on the switching intention, brand image positive and significant impact WOM mediate with the switching intention. Spread of WOM that can positively affect the brand image of Samsung better thus making consumers who do not use a smartphone Samsung has an interest to use a Samsung smartphone and future research are expected to use more sample size that covers an area larger research
Keywords: Brand image, WOM, Switching intention